Rozwój systemów informatycznych w kierunku inteligentnych systemów klasy ERP - Dudycz, Helena (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
Today's transactional information systems provide the enterprises with all the important information. But now the problem is to findi the most efficient way of using this information in order to optimize decision making. The main goal of this article is to analyse causes of development information systems towards intelligent enterprise resource planning (IERP). The first part briefly characterizes the conditions of development of system ERP. The next part describes new versions of ERP systems (named EERP, eERP, @ERP and IERP). The last part of this article contains the description of od causes of development information systems towards IERP. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Informatyka Ekonomiczna (9); 2006; nr 1144, s. 21-29